2017
DOI: 10.1007/s10815-017-0955-x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting embryos with the highest implantation potential using data mining and decision tree based on classical embryo morphology and morphokinetics

Abstract: In our decision tree, the classical morphological score is the most predictive parameter. Among embryos with better morphological scores, morphokinetics permits deselection of embryos with the lowest implantation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Several authors have indicated that morphokinetic parameters are characteristic of blastocyst formation (Wong et al , 2010; Conaghan et al , 2013; Milewski et al , 2015; Motato et al , 2016) and pregnancy or implantation (Meseguer et al , 2011; VerMilyea et al , 2014; Basile et al , 2015; Liu et al , 2016; Milewski et al , 2016; Motato et al , 2016; Petersen et al , 2016; Carrasco et al , 2017) but the general applicability of former morphokinetic algorithms for pregnancy, implantation or birth prediction is currently subject to controversy. Some authors who were not involved in developing the algorithms have maintained that time-lapse algorithms have a significantly higher predictive power than conventional scoring (Adamson, 2016; Kieslinger et al , 2016; Adolfsson et al , 2018; Liu et al , 2018), while other authors were unable to show a significant predictive capability for pregnancy, implantation or live birth (Kirkegaard et al , 2014; Yalçınkaya et al , 2014; Fréour et al , 2015; Ahlstrom et al , 2016; Goodman et al , 2016; Barrie et al , 2017; Adolfsson et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have indicated that morphokinetic parameters are characteristic of blastocyst formation (Wong et al , 2010; Conaghan et al , 2013; Milewski et al , 2015; Motato et al , 2016) and pregnancy or implantation (Meseguer et al , 2011; VerMilyea et al , 2014; Basile et al , 2015; Liu et al , 2016; Milewski et al , 2016; Motato et al , 2016; Petersen et al , 2016; Carrasco et al , 2017) but the general applicability of former morphokinetic algorithms for pregnancy, implantation or birth prediction is currently subject to controversy. Some authors who were not involved in developing the algorithms have maintained that time-lapse algorithms have a significantly higher predictive power than conventional scoring (Adamson, 2016; Kieslinger et al , 2016; Adolfsson et al , 2018; Liu et al , 2018), while other authors were unable to show a significant predictive capability for pregnancy, implantation or live birth (Kirkegaard et al , 2014; Yalçınkaya et al , 2014; Fréour et al , 2015; Ahlstrom et al , 2016; Goodman et al , 2016; Barrie et al , 2017; Adolfsson et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, time-lapse imaging (TLI) systems have been developed, giving embryologists the chance to use additional non-invasive criteria. Several markers of embryonic kinetics (Lemmen et al , 2008; Abeyta and Behr, 2014; Armstrong et al , 2015) have been studied from the first cleavage onwards, and some of them have been applied in decisional algorithms for embryo transfer (Meseguer et al , 2011; VerMilyea et al , 2014; Basile et al , 2015; Liu et al , 2016; Milewski et al , 2016; Petersen et al , 2016; Carrasco et al , 2017). However, there is still a need to determine whether kinetic parameters can be used as independent criteria to improve embryo selection (Goodman et al , 2016; Petersen et al , 2016; Armstrong et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of fertilization at a single time point, such as by observation of patterns of nucleolar precursor bodies (NPBs) or the presence of halos in cytoplasm, may predict IVF treatment outcome, but the effect is not always as expected [11,12]. Time-lapse embryo imaging enables non-invasive observation and setting of evaluation markers such as polar body extrusion, pronuclear formation, and cleavage times and patterns, as well as enabling identification of embryo quality and prediction of the pregnancy/implantation rate [13,14]. In-depth study of the fertilization process by time-lapse imaging shows a difference between normal and abnormal embryos in the mean duration of pronuclei fading (PNF) [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, DT can be combined with other decision techniques to improve the performance of the model. Carrasco et al (2017) developed a hierarchical model based on data mining and used DT to determine optimal embryonic morphokinetic parameters, which can make predictions for the selection of human embryos. The researchers found that the most predictive parameter is the classical morphological score.…”
Section: Overview Of the Ai In Reproductive Medicinementioning
confidence: 99%
“…Additionally, embryo assessment using the dynamic monitoring system (Time-Lapse (TL)) provides continuous information on the embryos’ developmental stage and morphokinetics, though the time-lapse algorithms remains questionable (Storr et al 2018); some researchers do noy consider it as evidence of the benefits for embryo election (Kaser & Racowsky 2014, Armstrong et al 2018). Carrasco et al (2017) retrospectively analyzed 800 human embryos with known implantation data in an incubator with Time-Lapse system. They developed a model based on the analysis of morphokinetic parameters and the embryo morphology assessment on D3.…”
Section: Ai Applications In Reproductive Medicinementioning
confidence: 99%